Assessing the Representation of Synoptic Variability Associated With California Extreme Precipitation in CMIP6 Models. Issue 6 (16th March 2021) - Norris, Jesse; Hall, Alex; Chen, Di; Thackeray, Chad W.; Madakumbura, Gavin D.
Abstract: Days of extreme precipitation over California are evaluated in Coupled Model Intercomparison Project Phase 6 (CMIP6) models and the ERA‐Interim reanalysis. In the current climate, the model spread in composited precipitation on extreme precipitation days is closely related to the magnitude of composited integrated vapor transport (IVT) across models, a proxy for the intensity of atmospheric rivers. Most models underestimate the magnitude of IVT associated with extreme precipitation, according to ERA‐Interim. This is due mostly to the contribution of moisture, which almost all models overestimate, while the contribution of lower‐tropospheric wind speed is generally closer to the reanalyses. Moreover, most models underestimate the variance in the latitude of maxima of numerous variables among days of extreme California precipitation. That is, in the general circulation models there is a lack of diversity in the latitude of the disturbances bringing winter precipitation to California. In the future climate, most models project a decrease in the frequency of southward‐displaced disturbances among California extreme precipitation days. Hence, the greatest increases in extreme precipitation are over northern California. However, the historical underestimate of the latitudinal variance of disturbances calls into question the reliability of these projections. This bias should be especially considered for dynamical downscaling efforts over the region. Key Points: Coupled Model Intercomparison Project Phase 6 models overestimate moisture and hence moisture flux associated with extreme precipitation over California, according to reanalyses General circulation models (GCMs) underestimate the variance in latitude of disturbances on California extreme precipitation days GCMs project future California extremes to be increasingly associated with disturbances centered farther north